Health Risk Assessment Due to Wastewater in Charm-Shahr Industrial Town of Mashhad - Somayeh Khojasteh; Azadeh Karimi (محیط زیست و توسعه فرابخشی)
Introduction: Over the past a few decades, human societies have observed that the concentrations of heavy metals in the environment have increased due to industrial development, mining exploration, smelting industries and sometimes due to accidental emissions. These activities have posed a major threat to the human’s health. Industrial towns are among the centers that, if not adequately monitored, can lead to the dispersion of heavy metals in the environment and endanger the health of people living in the surrounding area.Materials and Methods: For this purpose, the environmental hazards of wastewater from Charm-Shahr industrial town were investigated. In this study, the Risk Assessment Information System (RAIS) web-based software was used. The measured wastewater samples were analyzed between 2004 and 2019 and after pollutants’ identifications, non-carcinogenic hazards and carcinogenic risks of the human’s exposure to those pollutants were evaluated.Results:Based on the sampling from the outlet of Charm-Shahr’s water treatment plant, in most cases, the non-carcinogenic risk of exposure to the contaminants in water was less than 1, indicating that there is no significant risk to the residents in relation to the surface water of the exposure area. In one case, the non-carcinogenic risk of exposure to the contaminants in water from the oral path was in the range of 0.1 Discussion: According to the results, this risk was due to exposure to hexavalent chromium which was found in the sewage due to the presence of leather industries in Cahrm-Shahr. The rate of carcinogenic risk from both oral and skin pathways were in the range of  and . Therefore, there was a possibility of carcinogenesis in relation to the contaminants. The total risk was also in the range of  and , indicating the risk of total carcinogenesis was definite or probable, and in some cases, there was no known risk. Results showed that the existing health risk was due to the presence of hexavalent chromium and in some cases was related to nickel. It has been reported that chromium is sometimes converted to stable compounds with higher toxicity in the natural environment. In this study, we discussed the risk assessment due to the exposure of different groups of people and the impact on their health due to the concentrations of heavy metals resulting from industrial activities. The findings show that the carcinogenic risk was due to the presence of hexavalent chromium and in some cases nickel. The possibility of non-carcinogenic hazards and carcinogenic risks of exposure to hexavalent chromium and nickel were possible, probable and in some cases definite. Therefore, it is necessary to monitor the functionality of the Charm-Shahr’s water treatment plant and track the number of pollutants at specific time intervals. Periodic and continuous measurements of pollutants and the risk assessment due to the presence of hexavalent chromium and nickel pollutants on fish, other animals and plants in the region can be useful in controlling environmental pollution, providing monitoring programs and regional decision-making.